Demographic Profile of Drug-Resistant Tuberculosis Patients - Adi, Ricky Fernando; Jamilah, Yeni; Melati, Rima (Journal La Medihealtico, 2025)
Drug-Resistant Tuberculosis (DR-TB) represents a significant global health challenge with complex treatment and control issues. In Bekasi Regency, a metropolitan area with high population density, DR-TB incidence shows an increase requiring special attention. This study aims to identify the demographic profile of DR-TB patients to understand disease distribution characteristics and design appropriate management strategies. A descriptive study conducted at Bekasi Regency Hospital from October 2022 to October 2024. Data collected through MDR-TB outpatient medical records identified via Molecular Quick Test. Variables studied included age, gender, district of residence, and education level. Data analyzed using descriptive statistics and presented in tables, diagrams, and graphs. Among 338 DR-TB patients, the majority were aged 41-50 years (27.1%), with male patient dominance (61.5%). Tambun Selatan District had the highest cases (16.9%), with a population density of 10,063 people/km². Most patients were high school graduates (74.3%), with 89.6% originating from Bekasi Regency. The demographic profile of DR-TB patients at Bekasi Regency Hospital shows patterns similar to general tuberculosis cases. Tambun Selatan District exhibits the highest spread risk, indicating the need for targeted interventions in DR-TB prevention and control.